Using computers to enhance peer-assessment activities: towards a flexible e-assessment system - AL-Smadi, M.; Guetl, Christian; Helic, D. (International Association of Online Engineering, 2009)
Since the beginning of the 21st century, the learning process has changed from being repetitive to a new form of learning based on understanding, independency, learners' empowerment and skills improvement. As a main part of this learning process assessment is no more considered to discriminate between students, rather that it is used to enhance students learning and encourage them for further progress and success. In this new culture of assessment, teachers are no more considered to be knowledge carriers which they had to transfer to students' heads. Instead of that, students play major roles in assessment where new forms of assessment such as self-, and peer-assessment have been adapted. In this paper, we will address an enhanced approach of web-based peer assessment for short free text answers. This approach is supposed to motivate students to participate in the assessment process, provide them with added value learning, as well as to maintain the reliability of the peer-assessment results. An experiment using this web-based system was conducted and valuable results were found.